Transjugular Retrograde Obliteration prior to Liver Resection for Hepatocellular Carcinoma Associated with Hyperammonemia due to Spontaneous Portosystemic Shunt - Fumio Chikamori; Nobutoshi Kuniyoshi (Case Reports in Hepatology)
A 67-year-old woman had hepatocellular carcinoma (HCC) measuring 3.7 cm at S8 of the liver with hyperammonemia due to a spontaneous giant mesocaval shunt. Admission laboratory data revealed albumin, 2.9 g/dL; total bilirubin, 1.3 mg/dL; plasma ammonia level (NH3), 152 g/dL; total bile acid (TBA) 108.5 μmoL/L; indocyanine green retention rate at 15 min (ICG15), 63%. Superior mesenteric arterial portography revealed a hepatofugal giant mesocaval shunt, and the portal vein was not visualized. Before surgery, transjugular retrograde obliteration (TJO) for the mesocaval shunt was attempted to normalize the portal blood flow. Via the right internal jugular vein, a 6 F occlusive balloon catheter was inserted superselectively into the mesocaval shunt. The mesocaval shunt was successfully embolized using absolute ethanol and a 50% glucose solution. Eleven days after TJO, NH3, TBA, and ICG15 decreased to 56, 44, and 33, respectively. Superior mesenteric arterial portography after TJO revealed a hepatopetal portal flow. Partial hepatectomy of S8 was performed 25 days after TJO. The subsequent clinical course showed no complications, and the woman was discharged on postoperative day 14. We conclude that the combined therapy of surgery and TJO is an effective means of treating HCC with hyperammonemia due to a spontaneous portosystemic shunt.